Effect of urogastrone on gastric secretion and plasma gastrin levels in normal subjects. Issue 11 (November 1975) - Elder, J B; Ganguli, P C; Gillespie, I E; Gerring, E L; Gregory, H
Abstract : Purified human urogastrone was given by intravenous infusion to 12 normal volunteer subjects and measurements made of gastric acid, pepsin and intrinsic factor secretion, and of plasma gastrin concentration. Clinical, haematological, and biochemical screening tests were made throughout the period of study. Urogastrone inhibited acid and intrinsic factor secretion whether stimulated by pentagastrin, histamine, or insulin, but had a much less marked effect on gastric pepsin output. Plasma gastrin levels did not alter significantly. Limited dose-response studies showed that 0-25 mug urogastrone kg–1 hr–1 resulted in inhibition of acid output of 80% and was not associated with clinical side-effects. No significant alteration in any of the haematological or biochemical measurements was observed in any of the subjects.